а) х2+5х-14=(х-2)(х+7);
х2+5х-14=0;
д=25-4*(-14)=25+56=81;
х1=(-5+9)/2=4/2=2;
х2=(-5-9)/2=-14/2=-7;
б)16х2-14х+3=16(х-0,5)(х-0,375);
16х2-14х+3=0
д=(-14)2-4*16*3=196-192=4;
х1=(14+2)/32=16/32=0,5;
х2=(14-2)/32=12/32=0,375;
в)(3у2-7у-6)/(4-9у2)=3(у-3)(у+2/3)/-9(у-2/3)(у+2/3)=3(у-3)/(6-9у)=
(3у-9)/(6-9у)=3(у-3)/3(2-3у)=(у-3)/(2-3у);
3у2-7у-6=(у-3)(у+2/3);
3у2-7у-6=0
д=49-4*3*(-6)=49+72=121;
у1=(7+11)/6=18/6=3;
у2=(7-11)/6=-4/6=-2/3;
4-9у2=-9(у-2/3)(у+2/3);
4-9у2=0
9у2=4
у1=4/9=2/3;
у2=-2/3.
а)
8x^2-4x-x^2+9
7x^2-4x+9
b)(р+3)(р-11)+(р+6)²
p^2 -8p-33+ p^2+12p+36 = 2p^2+4p+3
в)7(а+b)²-14 ab
7a^2+14ab+7b^2-14ab=7a^2+7b^2
2. Разложите на множители:
а) γ³-49γ ; б) -3а²-6ab-3b²
a)y(y^2-49)=y(y-7)(y+7)
б) -3а²-6ab-3b² =-(3a^2+6ab +3b^2)=-3(a+b)^2
3. Упростите выражение:
(а-1)²(а+1)+(а+1)(а-1) и найдите его значение при а= -3
16*-2+8=-32+8 =-24
а) (γ-6)²-(3γ)² = (y-6-3y)(y-6+3y)
б) с²-d²-c-d =(c-d)(c+d) - (c+d)=(c+d)(c-d-1)
(х-γ)² + (х+γ)²=2(х²+γ²)
x^2-2xy+y^2+x^2+2xy+y^2=2(x^2+y^ 2)
2x^2+2y^2=2 (x^2+y^2)
2x+4+6=247
Объяснение:
Без x надо писать